Exaggerated platelet reactivity in major depression - Musselman, D L; Tomer, A; Manatunga, A K; Knight, B T; Porter, M R; Kasey, S; Marzec, U; Harker, L A; Nemeroff, C B (The American journal of psychiatry, 1996)
This study investigated whether depressed patients exhibit exaggerated platelet reactivity. In vivo platelet activation, secretion, and dose-response aggregation were measured in 12 depressed patients and eight normal comparison subjects after overnight bed rest and following orthostatic challenge. The depressed patients exhibited increased platelet activation at baseline, demonstrated by increased binding of monoclonal antibody (moAb) annexin V protein reacting with prothrombinase complex binding sites. Following orthostatic challenge, the depressed patients exhibited increases in binding of moAbs PAC1 and anti-LIBS1 against activated glycoprotein IIb/IIIa and GE12 against P-selectin expressed upon secretion. The normal comparison subjects exhibited increases in platelet activation only with GE12. Depressed patients exhibit enhanced baseline platelet activation and responsiveness in comparison with normal subjects. Heightened susceptibility to platelet activation may be a mechanism by which depression is a significant risk factor for ischemic heart and cerebrovascular disease and/or mortality after myocardial infarction.